Cognitive Acceleration through Science Education (CASE) program: Accelerating students’ cognitive development - Chandra Adi Prabowo; Wahyu Widodo (University of Muhammadiyah Malang, 2019)
As an intervention program developed to accelerate participant cognitive development, the effect of Cognitive Acceleration through Science Education (CASE) implementation in certain conditions needs to be clarified. This paper describes the effect of CASE program to the cognitive development of elementary students in Indonesia. The study used a mixed method sequential explanatory design with the quantitative data collection in the first phase by Scientific Reasoning Skill Tasks administered to all of participants both before and after intervention followed by collection of qualitative data in the second phase included interviews with the participants from both CASE and control groups. Participants of the study were 70 elementary school students (aged 10-12). After three months of intervention, students of CASE group showed higher mean gain (RGS mean= 4.4) compared to those of control group (mean RGS = 0.1). The qualitative data indicated that the CASE program also enhanced students’ motivation. Moreover, teachers who involved in the Teachers’ Professional Development (PD) Training Program developed more specific strategy to enhance student’ cognitive ability. In other words, the CASE program was a worthwhile intervention for elementary level students in Indonesian school.